EDUKASI TEKNOLOGI PANEL SURYA SEBAGAI SUMBER ENERGI LISTRIK AQUAPONIK DI KELURAHAN TANJUNG PALAS KOTA DUMAI - Bobby Demeianto; Rizqi Ilmal Yaqin; Muhammad Nur Arkham; Bambang Imawan; Kenny Bastian; Iwed Mulyani (Pusat Pengabdian kepada Masyarakat LP2M UIN Sunan Gunung Djati Bandung, 2021)
The source of electrical energy is one of the main components in everyday life. The development of technology today requires all people to be able to take advantage of renewable energy, one of which is solar energy. The solar panel is an energy conversion machine that can produce electrical energy. Coastal communities have an abundance of solar energy sources that can be utilized by solar panels as alternative electrical energy in the aquaponics system that has been built. The majority of the people of Tanjung Palas Village, Dumai City, are fishermen. So that there is a need for additional economic income besides being a fisherman. On the other hand, the community still does not understand the operation and maintenance of solar panels due to knowledge problems. Therefore education and the installation of solar panels as a source of aquaponic electricity are alternative solutions offered to the community. The educational activity of solar panels as a source of aquaponic electricity is carried out in collaboration with CSR PT Pertamina RU II Dumai with the Dumai Marine and Fisheries Polytechnic. The result of this activity is that the level of understanding of participants from per category always increases. The knowledge category increased from 39% of participants to 93% of participants, the operating category increased from 14% of participants to 94% and the care category increased from 14% of participants to 95% of participants. In addition, the level of satisfaction of the participants shows that 25% of participants are very satisfied and 75% of participants are satisfied with this activity. Recommendations for the results of activities that have been carried out are that there is a need for follow-up activities so that the community can better utilize solar panels as alternative electrical energy.